Myofascial Pain - Weller, Jason L.; Comeau, Douglas; Otis, James A.D. (Seminars in Neurology, 2018)
Myofascial pain syndromes arise from acute and chronic musculoskeletal pain and often have a referred neuropathic component. It affects more than three quarters of the world's population and is one of the most important and overlooked causes of disability. The origins of pain are thought to reside anywhere between the motor end plate and the fibrous outer covering of the muscle, with involvement of microvasculature and neurotransmitters at the cellular level. Diagnosis is made by clinical examination for the presence of myofascial trigger points, though some ancillary tests may provide supportive evidence. The mainstay of treatment is regular physical therapy with the goal of restoration of normal muscle laxity and range of motion. Adjunct therapies including pharmacologic and nonpharmacologic interventions provide varying degrees of benefit in refractory cases, and onabotulinum toxin A injection has the most evidence of efficacy for these patients. Here, we discuss the epidemiology, pathophysiology, and diagnostic and therapeutic options for the evaluation and treatment of myofascial pain syndrome.
Keywords: myofascial; trigger points; onabotulinum toxin